Historical Dictionary of Children's Literature - O'Sullivan, Emer (Rowman & Littlefield Publishers, 2023)
History is constantly evolving, and the history of children’s literature is no exception. Since the original publication of Emer O’Sullivan’s Historical Dictionary of Children’s Literature in 2010, much has happened in the field of children’s literature. New authors have come into print, new books have won awards, and new ideas have entered the discourse within children’s literature studies. Historical Dictionary of Children's Literature, Second Edition contains a chronology, an introduction, and an extensive bibliography. The dictionary section has more than 700 cross-referenced entries. This book will be an excellent resource for students, scholars, researchers, and anyone interested in the field of children’s literature studies.